رسالة في أحكام الصبي المميز في النكاح لعبد الرحمن بن عبدالله النجدي ( ت 1274 هـ) : دراسة وتحقيق - النجدى، عبدالرحمن بن عبدالله، ت. 1274 هـ.; الهيتي، مجاهد محمود إسماعيل; الهيتي، فراس مجيد عبدالله (جامعة الأنبار - كلية العلوم الإسلامية, 2011)
هذه "رسالة في أحكام الصبي المميز في النكاح" للإمام عبد الرحمن بن عبد الله النجدي، وهو مخطوط فقهي على المذهب الحنبلي، بين فيه الأحكام المتعلقة بالصبي، منها: \ 1. أهليته في عقد الزواج، ومباشرته لعقد الزواج بنفسه، واهليته للطلاق. \ 2. عدة المطلقة من الصبي المميز. \ ٣. زواج التحليل من قبل الصبي المميز. \ 4. الأحكام المتعلقة بالخلع. \ وتبين من خلال عرضه للأقوال والاحكام بـــ: ((صحة نكاحه من وليه، تبين منه حالاً عند طلاقه، لا عدة عليها، أن لا يوجد تحليل في العقد، ان لا تكون عند الصبي نية بالتحليل اثناء العقد، تعتد بطلاقه إذا كان فوق العشرة سنين، وإذا تزوج لغرض التحليل فان انقضاء العدة حسب حالها، أن يجامعها في قبلها، أن يعقد عليها عقد جديد)). This is a letter in the regulations of the young boy in marriage by Imam Abdulrahman Bin Abdulah Al-Najdi which is a juristic manuscript according to Al-Hanbali creed in which he clarified the regulations that concern the young boy. \ Among them are:- \ -His competence in the marriage contract (bond) and practicing this bond by himself and his competence for divorce. \ -The period of waiting of the divorced (iddat) from the young boy. \ -The permitted marriage by the young boy. \ -The regulations that concern the divorce in return for monetary compensations to be paid by the wife to the husband. \ The following is concluded from his presentation of these sayings and regulations: \ (validity of his marriage by the one who is responsible for him which is pointed out directly at the time of his divorce. She is freed from the iddat, there is no permission in the bond. The boy should not have an intension for the permission during the bond. She should have iddat if the boy is more than ten years old. If he has got married for the permission (Al-Tahleel), then the end of iddat is according to its condition. He should have sexual intercourse with her from her front part and he should make a new bond with her.
Keywords: تحقيق المخطوطات -- الزواج ( فقه اسلامي) -- الخلع ( فقه اسلامي) -- الأحكام الشرعية -- النجدي ، عبدالرحمن بن عبدالله ، ت 1274 هـ -- تراجم -- النكاح -- الفقه الحنبلي -- الأدلة الشرعية -- التكليف ( فقه اسلامي)